Management of Primary Open Angle Glaucoma (POAG): Ayurvedic and Modern Approaches (AYUSHDHARA, 2023)
Primary open-angle glaucoma (POAG) is a chronic disease characterized by elevated intraocular pressure (IOP), optic nerve damage, and visual field loss. This review explores the management of glaucoma from both Ayurvedic and modern medical perspectives, discussing their similarities, differences, and potential benefits. Modern therapeutic approaches include medication, laser therapy, and surgery to lower IOP and prevent visual field damage. However, glaucoma progression and optic nerve damage can occur even with normal IOP levels. Ayurveda views POAG as a manifestation of Adhimantha, primarily involving Pitta and Rakta doshas. Ayurvedic treatments focus on improving ocular health through various therapies, herbal formulations, and lifestyle modifications. Integrating Ayurvedic and modern approaches may provide a comprehensive approach to glaucoma management, enhancing patient outcomes.